1985
DOI: 10.1172/jci112229
|View full text |Cite
|
Sign up to set email alerts
|

In vitro prostacyclin production by ovine uterine and systemic arteries. Effects of angiotensin II.

Abstract: Normal pregnancy is associated with reduced systemic pressor responses to infused angiotensin II (ANG II); furthermore, the uterine vascular bed is even less responsive to vasoconstriction by ANG II than the systemic vasculature overall. The mechanism(s) for this refractoriness remains unknown. To in P and early uterine arteries only; the threshold dose was between 5 X 10-" and 5 X 10-9 M ANG II. This ANG II-induced increase in 6-keto-PGFI. by uterine arteries was inhibited by Saralasin, which by itself had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…At the end of the preincubation period the media was replaced with fresh oxygenated Krebs-Henseleit buffer and a 2-h incubation was performed, exchanging the buffer each hour to determine if substrate availability was rate limiting (21). As we have done previously in studies of other arteries (21), hyperoxic conditions were employed in vitro to maintain the degree of oxygenation at a level at which oxygen availability would not limit PG production (22,23). Selected segments were incubated in the presence of 100 MuM indomethacin to confirm that the PGs measured were newly synthesized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the preincubation period the media was replaced with fresh oxygenated Krebs-Henseleit buffer and a 2-h incubation was performed, exchanging the buffer each hour to determine if substrate availability was rate limiting (21). As we have done previously in studies of other arteries (21), hyperoxic conditions were employed in vitro to maintain the degree of oxygenation at a level at which oxygen availability would not limit PG production (22,23). Selected segments were incubated in the presence of 100 MuM indomethacin to confirm that the PGs measured were newly synthesized.…”
Section: Methodsmentioning
confidence: 99%
“…Samples ofthe incubation media were assayed for the stable metabolite of prostacyclin, 6-keto-prostaglandin Fla, and for PGE2 by radioimmunoassay as previously described (21,24 and the tubes were incubated, bound and free ligand were separated, and bound ligand was quantified as in the 6-keto-PGFa assay. The unknown quantities of 6-keto-PGFia and PGE2 were determined from the standard curves generated.…”
Section: Methodsmentioning
confidence: 99%
“…Magness et al (30,31) suggested that increases in basal and ANG II-mediated synthesis of endothelium-derived prostacyclin (PGI 2 ) and/or nitric oxide (NO) contribute to the attenuated ANG II contractions in the pregnant ovine UVB. Alternatively, the pregnancy-related rise in plasma ANG II levels could decrease ANG II receptor (ATR) expression and/or binding and alter vascular responsiveness (29,32).…”
mentioning
confidence: 99%
“…The incubation procedures employed were similar to those we have used in studies of uterine and systemic arteries from pregnant sheep (22). After collective equilibration, the segments were placed individually into sealed polypropylene chambers containing 2.0 ml of oxygenated (680 mmHg) KrebsHenseleit buffer at 37°C for 1 h. At the end of this preincubation period, the media was replaced with fresh Krebs-Henseleit buffer and a 5-20-min incubation was performed.…”
Section: Methodsmentioning
confidence: 99%